2016
DOI: 10.1007/s11187-016-9780-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of habitual entrepreneurial experience on new firm closure outcomes

Abstract: In this paper, we argue that it is difficult for habitual entrepreneurs to use their experiential knowledge to develop a more viable new firm than novice entrepreneurs. Hindered by the difficulty of disentangling how actions lead to outcomes in low predictive environments such as new firm settings; hampered by the novelty and uncertainty of new firm closure; and misguided by subjective beliefs about their ability, we contend that habitual entrepreneurs close their new firm just as quickly as novice entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…Our study complements the findings of Gottschalk et al (2017) in a low-tech context such as franchising relationships.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our study complements the findings of Gottschalk et al (2017) in a low-tech context such as franchising relationships.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, Michael (2000) showed that previous experience of franchisees may increase litigation by enhancing franchisees' bargaining power and hindering possible agreements with franchisors. More generally, Gottschalk et al (2017) found no advantage of habitual entrepreneurs over novice entrepreneurs in terms of survival, although those with industry experience tend to survive longer. We interpret that franchise ventures represent original templates and past industry experience does not help to disentangle the causes of business success.…”
Section: Discussionmentioning
confidence: 85%
“…Recipients of only loans have a slightly lower merger probability, so mergers may be a way for nonsubsidized firms to overcome financial constraints (Table 4a). Finally, we find a larger although weakly significant likelihood of business failure defined as the event of declaration of bankruptcy following the definition by (Gottschalk et al, 2017) for treated firms than for the untreated firms. This suggests that in our data, unlike in the study by Conti (2018) for Israeli firms, subsidies do not reduce the likelihood of failure per-se, perhaps because subsidized ventures tend to carry out riskier projects.…”
Section: Crowding Out Of Private Investmentmentioning
confidence: 64%
“…High-skilled entrepreneurs become serial entrepreneurs through constantly looking for high-quality ventures that generate a high expected value (profit), whilst low-skilled ones will not become serial entrepreneurs. However, such a formal model does not square very well with the existing evidence where low-skilled individuals often seem to be driven out of the labour market and therefore engage in multiple or serial necessity-driven entrepreneurial activities (Gottschalk et al 2017). Parker (2014) developed a more comprehensive career choice model that allowed for the possibility that individuals may explore multiple entrepreneurial opportunities at the same time.…”
Section: Entrepreneurship As a Career Choicementioning
confidence: 85%